Campos basin: review on the geology and its oil and natural gas exploration and production context - De Jesus, Aline; Cardoso Vilela, Pamela (Latin American Journal of Energy Research, 2023)
This review and analysis work presents the Campos Basin, in its geological aspects, such as the tectonosedimentary evolution and its petroleum systems and exploratory plays, the history of exploration and production, in post-salt and pre-salt reservoirs, the panorama current production as well as future perspectives for production in the basin, in the context of national medium and long-term forecasts.